Apolipoprotein E content of VLDL limits LPL-mediated triglyceride hydrolysis - Brynne E. Whitacre; Philip Howles; Scott Street; Jamie Morris; Debi Swertfeger; W. Sean Davidson (Journal of Lipid Research, 2022)
High levels of circulating triglycerides (TGs), or hypertriglyceridemia, are key components of metabolic diseases, such as type 2 diabetes, metabolic syndrome, and CVD. As TGs are carried by lipoproteins in plasma, hypertriglyceridemia can result from overproduction or lack of clearance of TG-rich lipoproteins (TRLs) such as VLDLs. The primary driver of TRL clearance is TG hydrolysis mediated by LPL. LPL is regulated by numerous TRL protein components, including the cofactor apolipoprotein C-II, but it is not clear how their effects combine to impact TRL hydrolysis across individuals. Using a novel assay designed to mimic human plasma conditions in vitro, we tested the ability of VLDL from 15 normolipidemic donors to act as substrates for human LPL. We found a striking 10-fold difference in hydrolysis rates across individuals when the particles were compared on a protein or a TG basis. While VLDL TG contents moderately correlated with hydrolysis rate, we noticed substantial variations in non-apoB proteins within these particles by MS. The ability of LPL to hydrolyze VLDL TGs did not correlate with apolipoprotein C-II content, but it was strongly inversely correlated with apolipoprotein E (APOE) and, to a lesser extent, apolipoprotein A-II. Addition of exogenous APOE inhibited LPL lipolysis in a dose-dependent manner. The APOE3 and (particularly) APOE4 isoforms were effective at limiting LPL hydrolysis, whereas APOE2 was not. We conclude that APOE on VLDL modulates LPL activity and could be a relevant factor in the pathogenesis of metabolic disease.